Improving 20 kVA Generator Power Performance by Rewinding the Stor Conductor Windings - Rianto Wijaksana Silalahi; Parlin Siagian; Haris Gunawan (Sean Institute, 2025)
The decline in power performance in generators can be caused by various factors, one of which is the degradation of the stator conductor windings due to age, excessive temperature, or unstable operational conditions. This study aims to analyze and improve the power performance of a 20 kVA generator through the rewinding process of the stator windings with new conductors that meet technical standards. In this study, the methods used include initial analysis of the condition of the old windings, planning the winding redesign, the rewinding process, and testing the results through measuring voltage, current, efficiency, and power factor. The test results show a significant improvement in generator performance parameters after the rewinding process. The output voltage becomes more stable, power losses decrease, and efficiency increases from 0% to 80%. In addition, the power factor has improved from 0 to 0.92. This improvement proves that the rewinding process with the right material and technical specifications can restore and even significantly improve generator performance. This study makes a real contribution to the maintenance and reconditioning of electrical equipment, especially in small-to-medium scale power generation systems.